Comparison of the Characteristics of Hydrochar and Torrefied-Char of Traditional Chinese Medicine Residues - Zhiqiang Xu; Wenyu Ren; Shiliang Wu; Rui Xiao (Energies)
With the continuous reduction in fossil energy reserves and the increasingly prominent negative impacts on the environment, the search for sustainable alternative materials has become an urgent task. Biomass-based char has attracted much attention in the field of environmental protection, due to its wide-ranging and renewable raw materials. Hydrothermal carbonization and torrefaction carbonization, as two important biomass carbonization processes, each have their own advantages. This study focuses on the millions of tons of Chinese medicine residue waste generated in China every year. Four common Chinese medicine residues, Shanyao (Chinese yam), Suoyang (Cynomorium songaricum), Yujin (Curcuma aromatica), and Xueteng (Spatholobus suberectus), were selected and treated by hydrothermal carbonization and torrefaction carbonization processes at temperatures of 240 °C, 260 °C, and 280 °C. Through analysis techniques such as Fourier-Transform Infrared Spectroscopy, X-Ray Diffraction, and Scanning Electron Microscopy, the changes in the crystal structure, chemical functional groups, and microscopic morphology of the carbonized products were deeply studied, and the carbon yield was measured. The research aims to reveal the carbonization laws of Chinese medicine residues, provide a scientific basis for their efficient resource utilization, and help promote the development of biomass-based carbon materials in the field of environmentally friendly materials, alleviating energy and environmental pressures.